Women as Opinion Leaders within Community (A Model of Feminism Perspective) - Lasmery RM Girsang (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2020)
Jakarta still faced many social problems. One of them related to urban settlement so that rusunawa was created to be a solution. In the beginning-unfortunately-the government’s policy had resulted in rejection among people living under the poverty line. It was caused by the difficulty of changing old habits from the previous location to a new situation. Besides that, phycological and economic burdens added serious problems for marginalized people. It happened until some women were aware of such a situation and put effort into the community. As a critical paradigm, this article discussed the Feminist Communication Theory to seek the role of voice in the construction of inequality and oppression. By using qualitative research, the results showed that through feminine transformative leadership, the informants were pushed to have abilities to communicate, dialogue, persuade, and influence the community to lead the community for having a new life world.